Implementation of Inclusive Education Policies for Persons with Disabilities - Nirmala, Bela; Febiana, Febiana; Salsabina, Salwa; Indraswari, Sri Primawati; Henda, Raden (Rechtsnormen: Journal of Law, 2025)
Background. Limited access to education for people with disabilities in Indonesia, especially in Cirebon City, is still a serious issue that causes social and economic inequality. Inclusive education is a strategic solution to ensure equal rights, but its implementation in the field is often not optimal. Purpose. This study aims to evaluate the implementation of inclusive education policies in SLB Negeri in Cirebon City based on effectiveness, efficiency, and responsiveness. Methods. The method used is normative juridical with a descriptive approach, focusing on Law No. 8 of 2016 and Cirebon City Regional Regulation No. 10 of 2023. Result. The study's results show that the policy has not been implemented optimally due to limited human resources, infrastructure, minimal teacher training, and complex bureaucracy. In addition, there is still inequality between Public and Private SLBs. Conclusion. Based on William N. Dunn's policy evaluation, this policy has been ineffective and unresponsive. It is necessary to increase the budget, train educators, simplify the bureaucracy, and strengthen the monitoring and evaluation system. Implementation. This study recommends improving regulations and cross-sectoral collaboration to ensure equal access to education for people with disabilities.